PROBLEM-BASED ENGLISH SPEAKING MATERIAL TO ENHANCE STUDENTS’ CRITICAL THINKING SKILLS - Nur Rahmawati; Ashadi Ashadi (Universitas Negeri Yogyakarta, 2018)
This study was aimed at examining the development of problem-based English speaking materials and the elements in the problem-based English speaking materials which can enhance grade X students’ critical thinking skills. Employing a Research and Development design using Jolly and Bolitho’s model (1998), the study collected data through observations, tests, interviews, and questionnaires to reach a comprehensive needs analysis. A total of 90 grade X students participated in the study. The product of this study was a set of supplementary materials for teaching speaking. Six units were developed; each of which consisting of six parts reflecting the problem-based stages. Based on the expert judgment, the mean score for all chapters was 3.69, equivalent to the range score of 3.25 ≤ x ≤ 4 (very good). Chapter I and II were tried out to the students. The response showed that the mean score of each chapter was 3.2, equivalent to the range score of 2.5 ≤ x ≤ 3.24 (good). To conclude, the materials are appropriate to be used by 10th graders because it meets their needs and it is designed based on the current curriculum.MATERI BERBICARA BAHASA INGGRIS BERBASISKAN MASALAH UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITISAbstrakPenelitian ini bertujuan untuk mengetahui pengembangan materi berbicara bahasa Inggris berbasiskan masalah dan elemen-elemen dalam materi berbicara bahasa Inggris berbasiskan masalah yang dapat meningkatkan kemampuan berpikir kritis siswa kelas X. Dengan melakukan penelitian dan pengembangan dengan mengadaptasi model Jolly dan Bolitho (1998), data dalam penelitian ini dikumpulkan melalui observasi, tes, wawancara, dan angket untuk mendapatkan hasil analisis kebutuhan yang komprehensif. Siswa kelas X sejumlah 90 orangberpartisipasi dalam penelitian ini. Hasil dari penelitian ini adalah satu set materi pendukung untuk mengajar berbicara. Enam unit materi sudah dikembangkan. Setiap unit berisi beberapa bagian yang mencerminkan langkah dalam pembelajaran berbasis masalah. Berdasarkan penilaian ahli, nilai rata-rata dari semua unit adalah 3,69 yang ekuivalen dengan rentang 3.25 ≤ x ≤ 4 dengan kriteria “sangat baik”. Unit I dan II diujicobakan. Respons siswa menunjukkan nilai rata-rata masing-masing unit sebesar 3,2 yang ekuivalen dengan rentang 2.5 ≤ x ≤ 3.24 dengan kriteria “baik”. Kesimpulannya, materi yang sudah dikembangkan layak untuk digunakan karena sesuai dengan kebutuhan siswa dan kurikulum yang digunakan.